Factors Affecting The Employee Motivation at Non-Public Universities in Ho Chi Minh City - Cam, Tran Ai; Thuy, Nguyen Thi Ngoc (VNU Journal of Science: Education Research; Vol 40 No 1DO - 10.25073/2588-1159/vnuer.4813, 2024)
The purpose of this study was to identify factors affecting the motivation of white-collar workers at non-public universities and to propose some solutions and human management perspectives with the aim of boosting employees' work motivation, productivity, and quality. This research used a combination of qualitative and quantitative research methods. Raw data was collected through a survey of 359 employees working at non-public universities in Ho Chi Minh City. The results of the study indicated 07 factors influencing employees' motivation, as listed statistically from the most crucial to the least influential: i) Salary, Bonus, and Welfare Policies (beta = 0,295); ii) Training activities and promotion (beta = 0,273); iii) Relationship with colleges (beta = 0,186); iv) Relationship with superior (beta = 0,185); v) Working condition (beta = 0,130); vi) Achievement Recognition (beta = 0,104); and vii) Working features (beta = 0,099).